EFFECT OF DENTAL PROXIMAL RESTORATIONS ON PERIODONTAL HEALTH IN PATIENTS - Bushra Irum; Muhammad Asif; Bakhtawar Mumtaz; Naveed Aslam (Journal of Ayub Medical College Abbottabad, 2022)
Background: The oral cavity is colonized by more than 700 species of bacteria and hundreds of those can be present within oral biofilms. Objective was to determine the frequency of periodontal attachment loss in patients with dental proximal restorations. Methods: This cross-sectional study included 100 patients with Class II (mesial /distal or mesio-occluso-distal composite and amalgam restorations. The minimum duration of pre-existing restoration for which periodontal attachment loss was assessed was more than 3 months. Patients wearing orthodontic appliances, pregnant women, patients having systemic health problems with well-established links to periodontal diseases such as diabetes mellitus and patients who had received periodontal treatment within the last 3 months were excluded. Periodontal Pocket depth and bleeding on probing was recorded using WHO periodontal probe. Pocket depth greater than 3 mm was considered pathologic. The data were analyzed using the SPSS, version 20. Descriptive statistics were computed. Chi square test was applied to compare the effects of duration of restoration and type of teeth on periodontal attachment loss. Results: Of total 100 participants 65 (65%) were males and 35 (35%) were females. The mean age was 30.74±9.21 years. In 14% cases having class II or Mesio occluso distal restorations normal pocket depth was recorded while 86% had pathologic pockets. Teeth where proximal restorations were present for more than one year were most commonly associated (29%) with pathologic pockets followed by proximal restorations which were present for three months (25%). As the duration of proximal restoration increased, the frequency of periodontal pathologic pockets increased (p<0.001) The prevalence of periodontal pocket was more in molars than premolars (p<0.001). Conclusion: Proximal restoration can be a significant risk factor for periodontal disease. Strict oral hygiene, proper design of restoration margin and supportive periodontal therapy is the utmost responsibility of the clinician.